(untitled) (Asian Journal of Agriculture, 2023)
Abstract. Manai-Djebali H, Nait Mohamed S, Madrigal-Martínez M, Martínez-Cañas MA, Sánchez-Casas J, Ben Youssef N. 2023. Comprehensive characterization of Gerboui olive oil: Quality, composition and aromatic profile. Asian J Agric 8: 10-17. This study presents an in-depth analysis of Gerboui olive oil, a relatively lesser-known Tunisian variety. The investigation encompassed a thorough evaluation of key quality parameters, including acidity, peroxide value, ultraviolet absorbance, and fatty acid composition. The findings establish that Gerboui olive oil not only meets the stringent criteria set by the International Olive Oil Council for extra virgin olive oil but also exhibits remarkable qualities. It demonstrated a robust antioxidant capacity, with a DPPH (2,2-diphenyl-1-picrylhydrazyl) radical inhibition percentage of 94.93%. Furthermore, it boasts a substantial total phenolic content of 564.81 mg CA (caffeic acid)/kg and commendable oxidative stability, lasting 30.44 hours. The oil displayed exceptional resistance to oxidation, showcasing its potential as a premium product with potential health benefits. Additionally, the research delved into the fatty acid composition, highlighting the prevalence of unsaturated fatty acids, particularly oleic acid. The triacylglycerol profile revealed the presence of primary and secondary triacylglycerols, with notable triacylglycerols (TAGs) like Dilinoleoyl oleoyl glycerol (LLO) and Oleoyl linoleoyl oleoyl glycerol (OLO) found in substantial proportions at 5.04% and 17.84%, respectively. Trioleoyl glycerol (OOO) emerged as the most abundant TAG, constituting 30.07% of the TAG content, contributing to the oil’s distinct characteristics. Furthermore, the analysis of volatile compounds unveiled a complex aroma profile, with (E)-2-hexenal (19.47% ) and n-dodecane (15.66%) as the primary contributors. This comprehensive characterization enhances our understanding of Gerboui olive oil and underscores its potential as a unique and valuable olive oil variety.